I'm trying to understand the derivation of the Tsiolkovsky Rocket Equation. $$\Delta v= \int_{t_0}^{t_1} \dfrac{|T|}{m_0 - t\Delta m}dt$$ The Wikipedia page confused me here :

where $T$ is thrust, $m_{0}$ is the initial (wet) mass and Δm is the initial mass minus the final (dry) mass

Which means that $$m_0 - t\Delta m = m_0 -t(m_0-m_{dry})$$

If the rocket launched at $t_0=0$ seconds and reaches the dry mass at $t_1 = 60$ seconds, then at $t_1$ we should expect an acceleration of $$a(t_1) =\dfrac{|T|}{m_{dry}}$$ but we get $$a(t_1) =\dfrac{|T|}{m_{0} - t_1 \Delta m} = \dfrac{|T|}{m_{0} - 60s \Delta m} $$

I am unsure if this is an error or not. I then derived the equation using a slightly different approach I made up which seemed more intuitive to me, instead of using $\Delta m$, I used the rate $r$ (kg/s) at which the fuel exits the system.

$$\Delta v= \int_{t_0}^{t_1} \dfrac{|T|}{m_f - tr}dt$$

Now if I we take the integral we obtain

$$\Delta v =-\dfrac{|T|}{r}\ln\left|\dfrac{m_0}{m_{dry}}\right|$$

My derivation seems wrong because I have a negative sign in front which doesn't make sense. Is there something that I missed?

  • $\begingroup$ I would like to add one thing to CR drost's answer that it should be m_final=m_initial-dm/dt(time elapsed) in the wiki article $\endgroup$ Commented Nov 21, 2019 at 21:51

1 Answer 1


Yes, this is at present a low-quality derivation on Wikipedia. In particular the assembly $m_0 - t \Delta m$ is not dimensionally consistent if $t$ has any given units. One would instead write, say, $$\Delta v = \int_{t_0}^{t_1}\mathrm dt ~\frac{T}{m_0 - (m_0 - m_1)(t - t_0)/(t_1 - t_0)}.\tag{1}$$ And then this expression is properly $T/m_0$ at $t = t_0$ and $T/m_1$ at time $t=t_1.$

You are totally fine here to write $r = (m_0 - m_1)/(t_1 - t_0)$ to simplify; it also looks like you invented a new mass $m_f = m_0 + r~t_0$ which allows us to write this entire expression indeed as $$ \Delta v = \int_{t_0}^{t_1}\mathrm dt ~\frac{T}{m_f - r~t},\tag{2}$$ which is fine. That denominator is indeed still $m_0 + r~t_0 - r ~t_0 = m_0$ at $t=t_0$ and with some more work, $m_0 + r~t_0 - r~t_1 = m_0 - r(t_1 - t_0)$ which simplifies to $m_1$ at $t = t_1.$ Great, although I question the choice of the name $m_f$ since it might indicate to someone “final mass” instead of “fictitious mass at $t=0$,” which is what it is.

In fact I think it would be much easier if we simply defined $\tau = t_1 - t_0$ and took $t_0 = 0$ as an arbitrary zero, so that you simply have $\int_0^\tau \mathrm dt T/(m_0 - r~t)$ and you do not need to think about half of these details.

Anyway the proper evaluation of (2) involves a $u$-substitution where we define, say, $\mu = m_f - r~t$ and then $\mathrm d\mu = -r~\mathrm dt,$ which is probably where you are getting the minus sign from. The minus sign here is 100% correct; the endpoints are that $\mu(t_0) = m_0, \mu(t_1) = m_1$ as discussed above, so we will find$$ \Delta v = -\frac{1}{r}\int_{m_0}^{m_1}\mathrm d\mu ~\frac{T}{\mu} = -\frac Tr \ln\left(\frac{m_1}{m_0}\right),\tag{3}$$and the minus sign serves a crucial purpose here: this logarithm is a logarithm of a number between $0$ and $1$ and therefore it is a negative value; the minus sign makes it positive.

So as far as I can tell, your error was in finding these boundaries or some other elementary step after that; you effectively had that $m_f - r~t$ was $m_1 = m_\text{dry}$ at time $t = t_0$ and $m_0$ at time $t = t_1$ when it is exactly the opposite; the subscript $0$ marks the beginning instant and the subscript $1$ marks the ending instant.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.